Peptide Linker Affecting the Activity Retention Rate of VHH in Immunosorbents - Da Li; Jun Ren; Fangling Ji; Qiang Peng; Hu Teng; Lingyun Jia (Biomolecules, 2020)
VHH-based immunosorbents are an emerging and promising tool for the removal of toxic substances from plasma. However, the small size of VHHs is a double-edged sword, bringing both benefits and drawbacks to the immunosorbent. The small size of the VHH allows a higher coupling density, while the closer distance to the resin might create steric hindrance for paratope access. The latter could be avoided by inserting a linker between the VHH and the gel attachment site. Here, we report an approach to improve the activity retention of the immobilized VHH by selecting suitable linkers between the VHH and the site-specific immobilization site on the resin. Seven peptide linkers differing in length and flexibility were fused to the VHH and contained the formylglycine generating enzyme (FGE) recognition sequence. These constructs were expressed in the cytoplasm of bacteria and purified, the VHH production yield and affinity for its cognate antigen was measured. Furthermore, the fGly conversion, the immobilization of the aldehyde-containing nanobodies, the immobilization on resin and the antigen binding activity of the VHH-based immunoadsorbents was monitored. The VHH with longer and rigid, proline-rich linkers exhibited good expression yield of approximately 160 mg/L of culture, a fGly conversion of up to 100%, and the highest activity retention rate of more than 68%. This study unveiled two suitable linkers for the preparation of VHH-based immunosorbents that will assist the development of their clinical application.